Pulses improve the soil - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
International Workshop on Phosphorus Nutrition of Grain Legumes in the Semi-Arid Tropics in January 1990,